Crystal Structure of HAb18G/CD147: IMPLICATIONS FOR IMMUNOGLOBULIN SUPERFAMILY HOMOPHILIC ADHESION - Yu, Xiao-Ling; Hu, Tiancen; Du, Jia-Mu; Ding, Jian-Ping; Yang, Xiang-Min; Zhang, Jian; Yang, Bin; Shen, Xu; Zhang, Zheng; Zhong, Wei-De; Wen, Ning; Jiang, Hualiang; et al. (The Journal of biological chemistry, 2008)
CD147, a member of the immunoglobulin superfamily (IgSF), plays fundamental roles in intercellular interactions in numerous pathological and physiological processes. Importantly, our previous studies have demonstrated that HAb18G/CD147 is a novel hepatocellular carcinoma (HCC)-associated antigen, and HAb18G/CD147 stimulates adjacent fibroblasts and HCC cells to produce elevated levels of several matrix metalloproteinases, facilitating invasion and metastasis of HCC cells. In addition, HAb18G/CD147 has also been shown to be a novel universal cancer biomarker for diagnosis and prognostic assessment of a wide range of cancers. However, the structural basis underlying the multifunctional character of CD147 remains unresolved. We report here the crystal structure of the extracellular portion of HAb18G/CD147 at 2.8Å resolution. The structure comprises an N-terminal IgC2 domain and a C-terminal IgI domain, which are connected by a 5-residue flexible linker. This unique C2-I domain organization is distinct from those of other IgSF members. Four homophilic dimers exist in the crystal and adopt C2-C2 and C2-I dimerization rather than V-V dimerization commonly found in other IgSF members. This type of homophilic association thus presents a novel model for homophilic interaction between C2 domains of IgSF members. Moreover, the crystal structure of HAb18G/CD147 provides a good structural explanation for the established multifunction of CD147 mediated by homo/hetero-oligomerizations and should represent a general architecture of other CD147 family members.